STUDENTS’ ERRORS IN USING INFINITIVE AT SECOND YEAR STUDENTS OF SMK SWASTA AWAL KARYA PEMBANGUNAN (AKP) LUBUK PAKAM - Tarigan, Karisma Erikson (Kairos English Language Teaching Journal, 2020)
This study deals with student’s error on the use of Infinitive in written form. The purpose of this study is to find out the type of errors and the causes of errors. This study is carried out at SMK AWAL KARYA PEMBANGUNAN, Jl Pagar Merbau III Lubuk Pakam, to the second year students. There were Forty two students were taken as the sample which taken by cluster sampling technique. The instrument for collecting the data are written test and interview. The result of this study showed that the students made error in using infinitive. The type of errors They were error of addition (854 errors or 73.40%), error of omission (321 errors or 26.16%), error of selection (5 errors or 20.43%). The cause of error Ignore of Rule Restriction (5.73%), Incomplete Application of Rule (56%) and False Concept Hypothesized (37.98%).